The Influence of Promotion, Price Perception, and Brand Image on Purchase Decision for Walls Ice Cream in Surabaya - Mutadid Billah; Hery Pudjoprastyono (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study is to find out how Walls Ice Cream pricing perception and brand image affect consumers' decisions to buy in Surabaya. The research methodology employed is quantitative. The demographic for this study consisted of all individuals in the city of Surabaya who drink Ice Cream, with a total of 105 respondents. The data gathering process involved the distribution of questionnaires, while the data analysis was conducted using the Structural Equation Modeling (SEM) Partial Least Squares (PLS) technique with the Smart PLS software. The findings of this study suggest that the promotion of pricing perception and brand image plays a significant role in influencing the decision to purchase Walls Ice Cream in the city of Surabaya. The factors show that Walls Ice Cream in Surabaya City purchase decisions are positively and significantly impacted by them.